2017
DOI: 10.5709/acp-0215-9
|View full text |Cite
|
Sign up to set email alerts
|

Words That Move Us. The Effects of Sentences on Body Sway

Abstract: According to the embodied cognition perspective, cognitive systems and perceptuo-motor systems are deeply intertwined and exert a causal effect on each other. A prediction following from this idea is that cognitive activity can result in subtle changes in observable movement. In one experiment, we tested whether reading various sentences resulted in changes in postural sway. Sentences symbolized various human activities involving high, low, or no physical effort. Dutch participants stood upright on a force pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 45 publications
1
5
0
Order By: Relevance
“…This study found that, in language processing, when participants processed a word containing visual information, the processing of the following word containing auditory information was impaired, and vice versa (i.e., switching costs). This is also consistent with the embodied cognition, which holds that the sensorimotor simulation is involved in language processing (see Stins, Marmolejo-Ramos, Wenker, Hulzinga, & Cañal-Bruland, 2017). The modality switching costs that were found in perceptual stimuli (e.g., see a picture and then hear a sound) in previous studies were also observed in language processing (e.g., see a word containing visual information and then see a word containing auditory information) in the present study (Barsalou, 2009; Pecher et al, 2003; Spence, Nicholls, & Driver, 2001).…”
Section: Discussionsupporting
confidence: 87%
“…This study found that, in language processing, when participants processed a word containing visual information, the processing of the following word containing auditory information was impaired, and vice versa (i.e., switching costs). This is also consistent with the embodied cognition, which holds that the sensorimotor simulation is involved in language processing (see Stins, Marmolejo-Ramos, Wenker, Hulzinga, & Cañal-Bruland, 2017). The modality switching costs that were found in perceptual stimuli (e.g., see a picture and then hear a sound) in previous studies were also observed in language processing (e.g., see a word containing visual information and then see a word containing auditory information) in the present study (Barsalou, 2009; Pecher et al, 2003; Spence, Nicholls, & Driver, 2001).…”
Section: Discussionsupporting
confidence: 87%
“…Numbers of participants in the TB and FB conditions (n = 23 and n = 18, respectively) who provided fact-based, ability-based or mental-state-based reasons for the questions that sought explanations of why they went to open one box and did not go to open the alternative box. One participant in the TB condition did not answer these questions, and hence the coding of reasons in TB condition was based on data from 23 their own right side in anticipating that the agent would-from her perspective-go to the left-side box, and that adults leaned to their own left side when anticipating that the agent would-from her perspective-go to the right-side box, fits with computational and conceptual models suggesting that motor representations and processes may be able to remap the agent's allocentric frame of reference into subjects' own egocentric frame of reference [35]. There are, however, studies showing that the link between action observation/prediction and action execution can be motorically mapped in some somatotopic manner (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Second, we measured adult observers' motor-generated behavioural expectations by having participants stand on a Wii ™ balance board (WBB), to provide temporally and spatially sensitive information about rapid changes in distribution of the body's centre of pressure in an online manner. Studies show that the WBB can reliably detect how motor representations activated during action observation and processing can elicit corresponding structures in motor control, resulting in unintended behavioural changes in motor output such as postural adjustments [14,[21][22][23]. Studies also suggest that imagined movements produce subliminal electromyographic activity in the involved muscles and may be evidenced through perturbations in postural sway [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…). Indeed, as previously evoked, the language embodied (Rueschemeyr et al 2010) and intertwined to the motor system (Stins et al, 2017). These singular language effects could also be situated at the level of the mobilization of the motivation, attention, emotion, memory, and vision (Byalistok, 2017;Mishra, Srinivasan, & Huettig, 2015).…”
Section: Language and Mental Imagerymentioning
confidence: 87%
“…For example, Anciaux, Alin, Leher, and Mondor (2002), while using a Creole version of the MIQ (MIQ-C), observed that bilingual subjects aged from 14 to 16 reported more vivid visual images than participants aged from 11 to 13 whereas there was no difference in French with the French version of the MIQ (MIQ-F). Indeed, the language system is deeply intertwined to the motor system (Stins, Marmolejo-Ramos, Wenker, Hulzinga, & Cañal-Bruland, 2017), its processing is embodied (Rueschemeyr, Lindemann, van Rooij, van Dam, & Bekkering, 2010) and shares neural structures with other cognitive activities as mental imagery or conceptual knowledge (Gallese & Lakoff, 2005).…”
mentioning
confidence: 99%